1990
DOI: 10.1161/01.hyp.15.3.257
|View full text |Cite
|
Sign up to set email alerts
|

Renal functional reserve and microalbuminuria in offspring of hypertensive parents.

Abstract: Renal functional reserve, microalbuminuria, and plasma atrial natriuretic factor were measured in 21 offspring (9.5 +/- 0.5 years of age, mean +/- SEM) of hypertensive parents and in eight children (10 +/- 0.5 years of age) with no family history of hypertension who were used as a control group. Renal functional reserve was evaluated by measurement of the changes in creatinine clearance after an oral protein load of 45 g/m2. Atrial natriuretic factor levels were determined before and 60 minutes after the prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0
3

Year Published

1992
1992
2005
2005

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 14 publications
2
29
0
3
Order By: Relevance
“…Our observations are consistent with 2 previous studies of normotensive subjects with a family history of hypertension. 7,12 These findings contrast with other studies reporting normal GFR in subjects predisposed to hypertension. 8,11,[47][48][49] The reasons for the discrepancies are not immediately obvious, but the studies differ substantially in the populations examined, the definition of predisposition, the age of subjects, and the methods of measuring GFR.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Our observations are consistent with 2 previous studies of normotensive subjects with a family history of hypertension. 7,12 These findings contrast with other studies reporting normal GFR in subjects predisposed to hypertension. 8,11,[47][48][49] The reasons for the discrepancies are not immediately obvious, but the studies differ substantially in the populations examined, the definition of predisposition, the age of subjects, and the methods of measuring GFR.…”
Section: Discussionmentioning
confidence: 64%
“…[7][8][9][10][11][12] Few data exist in relation to extracellular fluids, but 1 study has suggested that exchangeable sodium is reduced in young hypertensive subjects. 13 Animal models of genetic hypertension show renal phenotypic abnormalities during the development of hypertension, but their exact nature depends on the specific strain.…”
mentioning
confidence: 99%
“…22 Lastly, it has been observed that normotensive children of hypertensive parents have increased urinary albumin excretion, which may further support the premise that microalbuminuria is an early finding in individuals with a predisposition to hypertension. 23 Although the aforementioned studies underscore an important role for the kidneys, the etiology of essential hypertension is almost certainly multifactorial. Accordingly, microalbuminuria may reflect additional processes that may contribute to both renal dysfunction and the pathogenesis of hypertension.…”
Section: Possible Mechanismsmentioning
confidence: 99%
“…Like in early diabetic renal disease, 48 microalbuminuria may be present in normotensive subjects with a genetic risk for hypertension. 49 - 50 According to this hypothesis, the increase in serum levels of atherogenic lipoproteins would be a consequence rather than the cause of microalbuminuria. In support of this notion is the evidence that urinary losses of large amounts of proteins may lead to increased serum levels of total and LDL cholesterol as well as Lp(a).…”
mentioning
confidence: 99%